2018
DOI: 10.3389/fmicb.2018.01127
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Candida albicans Transcription Factor RLM1 in Response to Carbon Adaptation

Abstract: Candida albicans is the main causative agent of candidiasis and one of the most frequent causes of nosocomial infections worldwide. In order to establish an infection, this pathogen supports effective stress responses to counter host defenses and adapts to changes in the availability of important nutrients, such as alternative carbon sources. These stress responses have clear implications on the composition and structure of Candida cell wall. Therefore, we studied the impact of lactate, a physiologically relev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 44 publications
2
11
0
Order By: Relevance
“…Gene expression analysis performed in cells growing under robenidine treatment identified the transcription factor Rlm1, which was significantly upregulated upon robenidine treatment. Rlm1 is reported to be involved in cell wall biogenesis for maintenance of cell wall integrity (Alam et al, 2011;Delgado-Silva et al, 2014;Oliveira-Pacheco et al, 2018). The increase of mannan component and decrease of chitin content were also consistent with the role of Rlm1 on regulation of cell wall integrity (Delgado-Silva et al, 2014).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Gene expression analysis performed in cells growing under robenidine treatment identified the transcription factor Rlm1, which was significantly upregulated upon robenidine treatment. Rlm1 is reported to be involved in cell wall biogenesis for maintenance of cell wall integrity (Alam et al, 2011;Delgado-Silva et al, 2014;Oliveira-Pacheco et al, 2018). The increase of mannan component and decrease of chitin content were also consistent with the role of Rlm1 on regulation of cell wall integrity (Delgado-Silva et al, 2014).…”
Section: Discussionsupporting
confidence: 71%
“…RNA-seq analysis revealed that the expression of the transcription factor Rlm1 (Supplementary Figure S4), a downstream effector of Mkc1, was increased up to eightfold after treatment with robenidine for 90 min. Rlm1 plays an important role in maintenance of cell wall integrity (Oliveira-Pacheco et al, 2018). Interestingly, the expression of RLM1 decreased when C. albicans was exposed to robenidine over a prolonged period of time (3-9 h).…”
Section: Robenidine Regulates Rlm1 Expression Downstream Of Mkc1mentioning
confidence: 99%
“…Despite this, Rlm1 was shown to regulate a small fraction of caspofungin-responsive genes, and its activators remain unknown [7]. Recently, Rlm1 was shown to play a role in cell wall remodeling and filamentation in C. albicans when yeast-form cells were grown in lactate as a carbon source [13].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Rlm1 was shown to play a role in cell wall remodeling and filamentation in C . albicans when yeast-form cells were grown in lactate as a carbon source [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some of these play important roles in hyphal formation, adhesion, drug resistance, and matrix production (all intrinsic characteristics of biofilms), as well as in stress adaptation. It is not surprising, then, that adaptation to specific environmental niches modulates the ability of cells to form biofilms and, consequently, to resist antifungals [54,55,58,59,[182][183][184].…”
Section: Environment-triggered Biofilm Formation and Antifungal Resismentioning
confidence: 99%